Histological and histomorphometric analyses of narrow implants, crestal and subcrestally placed in severe alveolar atrophy: a study in foxhound dogs. Issue 4 (9th February 2015) - Calvo‐Guirado, Josè Luis; Delgado Ruiz, Rafael Arcesio; Ramírez‐Fernández, Maria Piedad; Abboud, Marcus; Janjic, Bojan; Maté Sánchez de Val, Jose Eduardo
Abstract: Background: Narrow‐diameter implants provide an alternative to the horizontal augmentation techniques situations severe bone atrophy. Lack of bone width and interdental space has been regarded as an encumbrance in the case selection for prosthetic rehabilitation using dental implants. Objective: The aim of the study was to evaluate bone‐to‐implant contact and marginal bone loss of two different narrow implants in resorbed ridges at different crestal positions. Material and methods: 48 Bredent Narrow ® implants (24 MiniSky ® and NarowSky ® ) were placed at crestal and subcrestal levels in healing bone of atrophic alveolar ridge of 6 American foxhounds. Histological and histomorphometric analyses of osseointegration were carried out at 4 and 8 weeks. Results: Modeling in the marginal defect region was accompanied by marked decreases in the dimensions of both the buccal and the more lingual bone walls. Relative to BIC, significant differences were found in favor of subcrestal group, for both Narrow Sky and MiniSky. Linear measurements showed to be slightly high in the crestal group. With significant differences for PM‐IS (peri‐implant mucosa to implant shoulder) and IS‐BC (implant shoulder to buccal bone crest). Conclusions: Within the limitations of animal study, it can be stated that the NarrowSky(test group) crestal and subcrestal implants showed less crestal bone resorption, higher ISQ values and most BIC at 4 and 8 weeks of evaluation compared with MiniSky implants (control group). The design of the implants plays an important role in peri‐implant mucosa and crestal bone maintenance at 8‐week follow‐up period.